Literacy and language planning - Kaplan, Robert B. (Lenguas Modernas, 2017)
There are several complex issues to be considered in the formulation of language policy and literacy policy: first, the question of what language planning is and who does it; second, the question embedded in the history of human language and in the evolution of written language as well as in the functions that written language has over time taken over; and third, in the L2 situation, the question ofthe fit between the sub-varieties of each language and the functions allocated to the various sub-varieties. The problem is particularly complex in the domain of literacy, since a generalized literacy in an L2 introduced to a minority population does not in any way suarantee that the minority population will acquire access to the power language -that sub-variety which empowers native speakers of the L2 to manipulate the power structure to accomplish social and political ends, the absence of which in the minority population insures their disempowerment.